Gender differences in the Prevalence and Pattern of Disease Combination of Chronic Multimorbidity among Indian Elderly. - Sharma, Palak; Maurya, Priya (Ageing International, 2022)
Background: India is undergoing a huge demographic and epidemiological change, resulting in an increase in population ageing. With this, the number of people with co-existence of multiple chronic diseases is also set to rise. The present study aims to identify gender differential in the most prevalent combinations of chronic conditions among the elderly living with multimorbidity in India. This study also examines the factors affecting multimorbidity status among the Indian elderly. This study used the data from Building a Knowledge Base on Population Ageing in India (BKPAI), conducted in 2011. The presence or not of multimorbidity was considered as the outcome variable. The bivariate and logistic regression analysis was done to access the pattern and predictors of multimorbidity among the elderly. The relative risk of having different chronic conditions were calculated among the population with multimorbidity. The prevalence of most prevalent disease combinations among the overall population and multimorbidity group was also calculated. The overall prevalence of multimorbidity among the elderly was 32.96% and higher among women (34.69%). The most prevalent diseases among respondents with multimorbidity conditions were arthritis or rheumatism (54.75%), hypertension (45.79%), loss of all-natural teeth (32.94%), cataract (31.34%), diabetes (23.01%) and asthma (21.06%). The prevalence of arthritis or rheumatism, diabetes and hypertension were higher among women in the multimorbidity group than men of the same group. The relative risks for conditions like dementia, loss of all-natural teeth, depression, cerebral embolism, stroke or thrombosis and osteoporosis are higher in the multimorbidity group. Hence these conditions have a higher possibility to co-exist with other chronic conditions. The most prevalent combination of diseases in the multimorbidity group was arthritis, rheumatism or osteoarthritis, hypertension, and cataract (4.68%). The prevalence of this combination is higher among women than men (women: 5.79%, men: 3.30%). Age, gender, religion, wealth quintile, current working status, smoking, alcohol were significant determinants of multimorbidity among the elderly. Multimorbidity is an emerging issue and highly associated with ageing. There lie gender differences in the combination of diseases and their prevalence. Therefore, there is a need to strengthen healthcare services for both men and women using gender-specific analysis as both genders have different priorities regarding healthcare utilisation. One of the relevant implications based on our findings is that researchers and policymakers need to work together to develop effective intervention strategies separately for men and women, which will help to reduce the burden of multimorbidity in the population.